The first human report of Hyphopichia burtonii, initially misdiagnosed as sterile peritonitis in a patient on peritoneal dialysis - Chamroensakchai, Tamonwan (Med Mycol Case Rep, 2021)
This is the first human infection caused by Hyphopichia burtonii, resulting in peritonitis in a patient on peritoneal dialysis initially diagnosed as sterile peritonitis, resulting in delayed diagnosis and treatment. This pathogen posed a challenging diagnosis, causing low-grade peritonitis and difficulty to culture with standard bacterial broth. Moreover, automated platforms for pathogenic yeast identification could not specify the species, but broad-range PCR targeting rDNA followed by DNA sequencing successfully solved the etiology.